Pengaruh Komunikasi, Kompetensi, Dan Kedisiplinan Terhadap Kinerja Pegawai Pada Kantor Badan Perencanaan Penelitian & Pengembangan (Baperlitbang) Banjarnegara - Lustono Lustono; Anisa Desy Hasnaeni (Medikonis, 2019)
ABSTRACT The aims of this study are to know the influence of communication, competence, and employees discipline in the Departement of Planning, Research, and Development (BAPERLITBANG) officials’ performance in Banjarnegara toward employess performance. This study guessed that there are two things which influencing employees performance, they are, the lack of the effectively communication and the competence. It is because ideally the employees working in accordance with their competence but in the BAPERLITBANG office in Banjarnegara is still found the empoyees who working not in accordance with their competence. In addition, it is also expected that employees discipline also become the factor to their performance. in this study, the researcher found many problem related to the discipline of the officials. In this study, the method that is used for collecting data is saturated sampling technique and multiple linear regression analysis helped SPSS 16 program used to analyse the data. The result of the study showed that the variable of communication (X1), and competence (X2) do not influence partially to employees competence. But, there is an influence partially of discipline variable (X3) toemployees’ competence. The result of the determination coefficient (30,4%) showed that the ability of independent variables (employees communication, competence, and discipline) in explaining dependent variable (employees performance) are in small percentage and there are still other variables which is not include in this study.